The Role of Intraarterial Chemotherapy in the Management of Retinoblastoma - Aleksandra Pekacka (Journal of Ophthalmology)
Introduction. Retinoblastoma is the most common primary intraocular neoplasm in children. With the advances in medicine, the armamentarium of available treatment modalities has grown. Intraarterial chemotherapy is a relatively new treatment method with promising outcomes. The purpose of this literature review is to evaluate its role in the management of retinoblastoma. Methods. A systematic online search was conducted using Ovid Embase and Ovid Medline. The final results included 23 studies. The studies were published between 2011 and 2019. The studies evaluated the technical success rate of IAC, globe salvage rate, and ocular and systemic complications, as well as the occurrence of deaths, metastasis, and secondary neoplasms. In total, 1827 eyes with retinoblastoma were analysed. The follow-up was between 0 and 252 months. Results. Overall globe retention rate ranged from 30% to 100%. Sixteen out of 23 studies reported ocular salvage between 60 and 80%. Eyelid oedema and erythema were the most commonly reported ocular complications following IAC. The most common systemic complications included nausea, vomiting, and neutropenia. Metastases and deaths were reported in 6 out of 23 studies. Three studies reported the development of secondary neoplasms. The technical success rate of IAC procedure ranged from 91% to 100%. Discussion. The studies have shown that IAC is a safe and effective treatment for advanced retinoblastoma, especially group D. It allows to save the globe without compromising patients’ survival. Local and systemic complications are acceptable. The role of IAC in less advanced tumours is yet to be established. Future work should focus on conducting larger prospective studies with longer follow-up. Multiple novel therapies for the management of retinoblastoma are currently being tested, including angiogenic inhibitors and targeted agents. The results seem to be promising. Future advances require a further in-depth understanding of unique genetics of retinoblastoma and complex interactions between tumour cells and their microenvironment.